A Comparative Study of the Early and Short-Term Outcomes of Aortic Replacement in Patients with Stanford type A Aortic Dissection and Ascending Aortic Aneurysm. - Anwar, Erfan Omer; Haji Saeed, Shkar Raouf; ., Aram Baram (Kurdistan Journal of Applied Research, 2022)
Ascending aortic replacement is a challenging and complex surgery. The mortality, morbidity, and outcomes depend on the causes of the ascending aortic pathology and the type of operation. The research was conducted in a single-center, prospective, observational cohort study of patients undergoing ascending aortic replacement due to dissection or aneurysm. In the hospital, mortality, morbidity, and short-term outcomes were measured. A total of 85 patients were included in this study. Of them, 65.9% were male, and 34.1% were female. Thirty-three patients had Stanford type A aortic dissection (STAAD), whereas 52 had ascending aortic aneurysm (ASAA). Early mortality was (21.21% and 1.9%) for STAAD and ASAA, respectively, while the survival rate after one year was (75.8% and 96.15 %) for ascending dissection and aneurysm, respectively. The results of our study show higher early surgical mortality and morbidity and a lower short-term survival rate for STAAD surgery compared with ASAA surgery.